Leaching Cu from e-waste PCB using thiourea solution and oxidizing H2O2 - Tiara Triana; Soesaptri Oediyani; Rindang Puspa Rini; Tio Aji Pamungkas (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
Technological advances that occur in developed and developing countries impact increasing the amount of electronic waste (e-waste). In Indonesia, the growth rate of e-waste is predicted to increase by ±23.2% in 2028. The impact that e-waste can have on human health requires processing electronic waste such as printed circuit boards (PCBs) to reduce environmental pollution and economic benefits. PCB waste can be reprocessed because it contains Au, Ag, and Cu metals. The purpose of this study was to determine the effect of size, percent solids, the concentration of oxidizing agent H2O2, and the addition of oxidizing volume H2O2 to the amount of Cu extracted. The fire assay analysis results show that the mixed PCB waste contains 9.08% Cu. PCB waste leaching was carried out by agitation leaching method using thiourea solution. The leaching process was carried out with a size variation of 80; 100; 120#, a percent solids variation of 10; 15; 20 percent, an oxidizing concentration of H2O2 variation of 0.2; 0.4; 0.6 M, and the addition of an oxidizing volume H2O2 variation of 20; 28; 36 percent. Leaching was then performed for 6 hours at a rotation speed of 200 rpm, a temperature of 25°C, and a pH of 1-2. The leaching of mixed PCB waste resulted in 3.5% Cu in the leached solution with 10% solids percent and an additional 28% H2O2 oxidizing volume. PCB waste with the finest particle size of -120# and concentration of 0.4 M H2O2 produces Cu in the leached solution with 0.26%. Kemajuan teknologi yang terjadi pada negara maju maupun negara berkembang berdampak pada meningkatnya jumlah limbah elektronik atau e-waste. Laju pertumbuhan limbah elektronik di Indonesia telah diperkirakan akan mengalami kenaikan sebesar ±23,2% pada tahun 2028. Dampak yang dapat ditimbulkan dari limbah elektronik dapat menyebabkan gangguan pada kesehatan manusia, sehingga diperlukan adanya pengolahan limbah elektronik seperti printed circuit boards (PCB) untuk mengurangi pencemaran lingkungan serta keuntungan secara ekonomi yang didapatkan. Limbah PCB berpotensi untuk diolah kembali dikarenakan memiliki kandungan logam seperti Au, Ag, Cu, Sn, dll. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh ukuran, persen padatan, konsentrasi oksidator H2O2 dan penambahan volume oksidator H2O2 terhadap nilai persen ekstraksi Cu. Berdasarkan hasil analisis fire assay, limbah PCB campuran mengandung 9,08% Cu. Pelindian limbah PCB dilakukan dengan metode agitation leaching menggunakan larutan thiourea. Proses pelindian dilakukan pada variasi ukuran 80; 100; 120#, dengan variasi persen padatan sebesar 10; 15; 20% pada varisai konsentrasi oksidator H2O2 0,2; 0,4; 0,6 M serta penambahan volume oksidator H2O2 20; 28; 36%. Setelah itu dilakukan pelindian selama 6 jam, dengan kecepatan putaran 200 rpm pada temperatur 25°C dengan pH 1-2. Hasil penelitian pelindian limbah PCB campuran menghasilkan kadar Cu pada larutan hasil pelindian sebesar 3,5% dengan persen padatan 10% dan penambahan volume oksidator H2O2 sebesar 28%. Limbah PCB dengan ukuran -120# dengan konsentrasi H2O2 0,4 M menghasilkan Cu pada larutan hasil pelindian dengan kadar 0,26%.